Strategi Perencanaan Sistem Informasi Dan Teknologi Informasi Di Lingkungan Perguruan Tinggi - Agung Budi Prasetyo (Journal of Applied Informatics and Computing, 2018)
Nowadays, many universities trying to implement Information System and Information Technology to support academic activities, but the some how there is still lacking. The problems come up when universities was mistake when initialize of what they needs. Utilization of applications of SI / IT that are not yet optimal include the lack of contribution, integration and innovation is suspected to be the cause factor. The most important thing to plan SI / IT is understanding the current condition to initialize the business needs through SWOT and Critical Success Factors analysis. The analysis will generate McFarlan portfolio matrix to determine the required applications by dividing it into 4 quadrants: support, key operational, strategic and high potential. The result of this application portfolio planning is a list of required applications now, in the future and mapping each of the proposed applications based on each function or part of the organization. From that results is expected gradually all academic activities can be automated through the presentation of accurate information and up-to-date also able to provide one stop service for academic activities than it can reduce the operational costs to support academic activities.